Factors influencing the uptake of cardiac rehabilitation by cardiac patients with a comorbidity of stroke. (April 2020) - Harrison, A.S.; Gaskins, N.J.; Connell, L.A.; Doherty, P.
Abstract: Background: Cardiac rehabilitation (CR) is an effective complex intervention for people with coronary heart disease (CHD) which promotes healthy lifestyles, improves quality of life and reduces risk factors. Only 50% of UK eligible patients participate in CR, of which 5.3% have a comorbidity of stroke. Literature has identified parallels in aetiology and risk factors of CHD and stroke. Alongside emerging literature on the benefits of CR for stroke patients, this prompted this study to investigate CR uptake in people with comorbidity of stroke. Methods: Patients entered into the National Audit of Cardiac Rehabilitation (NACR) between 1st Jan 2013 and 30th Jan 2019 were included. Analysis included patient- and service-level characteristics identifying factors associated with uptake of CR by people with comorbid stroke using hierarchical logistic regression. Results: 6, 342 patients were included in the final analysis. This subpopulation was comparable with the wider CR and stroke populations. Main patient-level factors included age, ethnicity, deprivation and having a partner. Main service-level factors were presence of a multi-disciplinary team (MDT) and staff hours per patient. Conclusion: Patient and service-level factors contributed to the likelihood of a cardiac patient with comorbid stroke attending CR. The patient-level variables are consistent with wider literature on uptake, suggesting different models of delivery need to be explored to meet the population needs. CR programmes with a more comprehensive and well-resourced MDT are more likely to succeed in increasing the patient attendance with comorbidity of stroke. This highlights inequity of provision and requires strategies to overcome and influencing uptake.